2015
DOI: 10.1186/s13643-015-0083-6
|View full text |Cite
|
Sign up to set email alerts
|

Handling trial participants with missing outcome data when conducting a meta-analysis: a systematic survey of proposed approaches

Abstract: BackgroundWhen potentially associated with the likelihood of outcome, missing participant data represents a serious potential source of bias in randomized trials. Authors of systematic reviews frequently face this problem when conducting meta-analyses. The objective of this study is to conduct a systematic survey of the relevant literature to identify proposed approaches for how systematic review authors should handle missing participant data when conducting a meta-analysis.MethodsWe searched MEDLINE and the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…We identified 69 citations that fulfilled our eligibility criteria on this HIV topic with only 24 studies addressing the missing data problem on the estimation of HIV prevalence during analysis. The same trend of fewer studies addressing the missing data problem is observed in other design like clinical trials and HIV longitudinal studies measuring different outcome [72]. The major reason for the missingness was reported to be a refusal to consent for an HIV test, and with complete case analysis be the primary method of analysis used.…”
Section: Discussionmentioning
confidence: 77%
“…We identified 69 citations that fulfilled our eligibility criteria on this HIV topic with only 24 studies addressing the missing data problem on the estimation of HIV prevalence during analysis. The same trend of fewer studies addressing the missing data problem is observed in other design like clinical trials and HIV longitudinal studies measuring different outcome [72]. The major reason for the missingness was reported to be a refusal to consent for an HIV test, and with complete case analysis be the primary method of analysis used.…”
Section: Discussionmentioning
confidence: 77%
“…All missing data will be reported. We will conduct a sensitivity analysis with (1) best‐worst and (2) worst‐best scenarios if patients are lost to follow up: Best‐worst scenario: all patients lost to follow up in the intervention group have not had the outcome of interest, and all patients lost to follow up in the control group have had the outcome of interest Worst‐best scenario: all patients lost to follow up in the intervention group have had the outcome of interest, and all patients lost to follow up in the control group have not had the outcome of interest …”
Section: Methodsmentioning
confidence: 99%
“…Corresponding authors of the included trials with incomplete data including unclear risk of bias ratings will be contacted for additional data. Imputation of missing data will be considered …”
Section: Methodsmentioning
confidence: 99%